2018
DOI: 10.1186/s12891-018-2323-0
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for evaluating the effects of a foot-ankle therapeutic exercise program on daily activity, foot-ankle functionality, and biomechanics in people with diabetic polyneuropathy: a randomized controlled trial

Abstract: BackgroundDiabetic polyneuropathy (DPN) negatively affects foot and ankle function (strength and flexibility), which itself affects the daily physical activity and quality of life of patients. A physical therapy protocol aiming to strengthen the intrinsic and extrinsic foot muscles and increase flexibility may be a promising approach to improve lower-extremity function, prevent further complications, and improve autonomy for daily living activities in these patients. Thus, the inclusion of a specific foot-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 67 publications
(78 reference statements)
0
27
0
2
Order By: Relevance
“…Furthermore, additional benefits of foot‐ and mobility‐related exercises, such as on glucose control (eg, Otterman, et al), were not considered in this systematic review. With the positive findings on some outcomes, and the potential additional benefits on general health‐related parameters and quality of life following exercise, we expect foot‐ and mobility‐related exercises to become even more important in this field in the near future, and new trials are already underway (eg, Monteiro et al).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional benefits of foot‐ and mobility‐related exercises, such as on glucose control (eg, Otterman, et al), were not considered in this systematic review. With the positive findings on some outcomes, and the potential additional benefits on general health‐related parameters and quality of life following exercise, we expect foot‐ and mobility‐related exercises to become even more important in this field in the near future, and new trials are already underway (eg, Monteiro et al).…”
Section: Discussionmentioning
confidence: 99%
“…So rather than a shift towards an increased research priority of prevention, the prevention to healing ratio in RCTs was only 1:36 in the last 4 y. With two published trial protocols, 7,8 and some ongoing trials identified from our systematic review of the trial registries, 9 it is hoped that more than two RCTs on prevention will be published in the coming 4 y. However, the growing discrepancy over the last 4 y is concerning, and shows that diabetic foot ulcer prevention remains underexposed in research.…”
Section: Ulcer Prevention Is Still Underexposed In Researchmentioning
confidence: 99%
“…Apparently, the paucity of studies in this field remains. However, with some protocols for RCTs or descriptions of interventions published recently, and some other ongoing RCTs identified in our registry search, we hope that our next update will result in more included studies of high‐quality.…”
Section: Discussionmentioning
confidence: 99%